2020
DOI: 10.21203/rs.3.rs-34056/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Managing Patient Flows in Radiation Oncology - Reworking Existing Treatment Designs to Prevent Infections During the COVID-19 Pandemic at a German University Hospital

Abstract: Purpose Implementing active Patient Flow Management practices in a large University Hospital Radiation Oncology Department to prevent nosocomial infections of patients and personnel during the COVID-19 pandemic, while safely enable continuation of essential therapies and optimizing infrastructure utilization.Patients and methods Year-to-date intervention analyses of calender weeks 12 to 19 comparing years 2019 and 2020 inpatient and outpatient procedures evaluating active patient flow management effects on ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Another type of protocol that was developed during this time were safety protocols to ensure patients and staff remained safe from the COVID 19 virus. With the implementation of safety protocols for in-person visits, it was found that patients were more likely to stay on treatment regimens with the extra layer of protection these protocols provided [14,27,34,41]. Lastly a protocol theme was identified surrounding how to evaluate staffing levels to ensure that areas in high need of staff were assisted by areas with a lighter workload.…”
Section: Facilitator To Patient Throughput: Protocol Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Another type of protocol that was developed during this time were safety protocols to ensure patients and staff remained safe from the COVID 19 virus. With the implementation of safety protocols for in-person visits, it was found that patients were more likely to stay on treatment regimens with the extra layer of protection these protocols provided [14,27,34,41]. Lastly a protocol theme was identified surrounding how to evaluate staffing levels to ensure that areas in high need of staff were assisted by areas with a lighter workload.…”
Section: Facilitator To Patient Throughput: Protocol Developmentmentioning
confidence: 99%
“…For healthcare staff taking care of patients in the ambulatory setting, education and training pertained to learning new protocols and guidelines, providing education to patients, learning new technology platforms, and conducting research. At times, each day brought new requirements, warranting the creation of new protocols, methods and learning modules for safe patient care [14,15,20,32,39]. For those ambulatory settings conducting care virtually, new technology tools were implemented, requiring training of staff on how to use the new tools, such as Zoom and Microsoft Teams [15,23].…”
Section: Facilitator To Patient Throughput: Education and Trainingmentioning
confidence: 99%
“…Otherwise, expanding the target volumes may be necessary, especially where daily imaging is not practicable, which is the case in settings with reduced resources or high patient flow or particular circumstances, such as the coronavirus disease 2019 pandemic. 14 …”
Section: Introductionmentioning
confidence: 99%